The Effect of Garlic on Cholesterol Induced Hyperlipidaemia in Rabbits - Ahmed, Aftab Uddin; Begum, Syeda Farida; Naushaba, Humaira; Islam, Md Noor; Naher, Begum Shamsun (Ibrahim Medical College Journal, 2009)
An experimental biochemical study was made on rabbits to demonstrate the possible role of aqueous extract of garlic as an antilipidaemic agent in the prevention of hyperlipidaemia. Untreated rabbits on atherogenic diet showed worse lipidaemic status than the normal control ones, as evident in higher serum cholesterol, triglycerides (TG), low-density lipoprotein (LDL) and lower high-density lipoprotein (HDL) level. On the otherhand the rabbits on atherogenic diet treated with aqueous extract of garlic showed significantly better lipidaemic status. It is suggested that aqueous extract of garlic is an important determinant of serum lipid level, which is an antilipidaemic agent against the pathogenesis of atherosclerosis. Ibrahim Med. Coll. J. 2007; 1(1): 16-20 Key words: Garlic; Cholesterol; hyperlipidaemia doi: 10.3329/imcj.v1i1.2890